2009
DOI: 10.1007/s10517-009-0610-3
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Model for Hypoxic Type of Cell Metabolism Evaluated on Rabbit Cardiomyocytes

Abstract: Activity of the energy production system in rabbits myocardium was examined under various conditions of whole-body vibration. The energy-dependent response of native mitochondria from rabbit heart was studied polarographically using a Clark closed membrane electrode. In was established that the energy production system in rabbit myocardium was involved in organism's response to whole-body vibration. Functional changes in myocardial mitochondria were shown to depend on the mode of whole-body vibration (frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…The two most prominent features that can enhance each other during MI-induced cardiac injury are the physiological defects of the ischemic tissue and the sustained inflammatory response, which ultimately lead to heart failure. One of the major complications of MI treatment is hypoxia-induced cardiomyocyte death (30). Previous studies have shown that protection of cardiomyocytes from hypoxia-induced injury could lead to a potential treatment for MI (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The two most prominent features that can enhance each other during MI-induced cardiac injury are the physiological defects of the ischemic tissue and the sustained inflammatory response, which ultimately lead to heart failure. One of the major complications of MI treatment is hypoxia-induced cardiomyocyte death (30). Previous studies have shown that protection of cardiomyocytes from hypoxia-induced injury could lead to a potential treatment for MI (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Вібрація -фізичний стрес, який викликає різноманітні нейровегетативні і соматичні реакції в організмі людини, а її біологічні ефекти можуть бути зумовлені як прямою дією на клітини і субклітинні структури, так і опосередкованою -через нейрогуморальні та нейрорефлекторні механізми [2]. Залежно від частоти коливань (від 10-15 до 15-50 Гц) вібрація спричиняє різний вплив на організм спортсмена, а саме, викликає збільшення поглинання кисню тканинами, оксигенації крові та м'язів, локальної і загальної циркуляції крові, а також активує м'язові ферменти, підвищує збудливість центральної нервової системи і артеріальний тиск [3]. Отже зрозуміло, що фізіологічну реакцію біологічної системи на зовнішні подразники слід розцінювати як наслідок процесів, які відбуваються на клітинному рівні.…”
Section: вступunclassified